Road expansion risk predicts future hotspots of tropical deforestation - Jayden E. Engert; Carlos M. Souza; Fritz Kleinschroth; F. Yoko Ishida; Stefany P. Costa; Jonas Botelho; William F. Laurance (Proceedings of the National Academy of Sciences, 2025)
Roads act as conduits for human incursions and hence underlie many of humanity’s impacts on nature, including deforestation, wildfires, and natural-resource overexploitation. Unfortunately, existing roadmaps often drastically underestimate the true extent of road networks and future predictions of road-related impacts rely on incomplete and outdated data, undermining development planning and conservation decision-making. Here, we develop a multivariate “road expansion risk” index to identify areas prone to road building and therefore vulnerable to road-related environmental impacts. Using a massive road dataset—137 million 1-ha raster cells drawn from three different sources arrayed across the Amazon and Congo basins and insular Asia-Pacific region—we predict road-prone locations via a statistical model that integrates a range of biophysical, socioeconomic, and administrative data. This highly integrative, large-scale approach allowed us to identify areas likely to experience future road building and regions that may contain unmapped roads. Importantly, our road expansion risk index is a strong predictor of forest loss and degradation and can hence identify future road building and deforestation hotspots, even for the many tropical forest locales with grossly deficient road data.